Newly undergraduate nurses and intensive care in units of non-critical patients - Rute de Oliveira Almeida; Francimar Tinoco de Oliveira; Márcia de Assunção Ferreira; Rafael Celestino da Silva
ABSTRACT Objective: To identify the social representations of newly undergraduate nurses on the intensive care of Nursing to critical patients hospitalized in non-critical patient units. Method: Qualitative and descriptive research. Twenty-six newly undergraduate nurses from a private university participated. An in-depth interview was conducted with semi-structured script. The analysis was of lexical type with the help of Alceste 2012 software. Results: The social representations were built according to the image of the intensive care unit, although patients were out of this environment. Care is understood as complex and specialized, requiring graduate training. Therefore, undergraduation training was considered insufficient to provide this type of care, creating fear and insecurity in the newly undergraduate nurses. Final considerations: Intensive care confronts newly undergraduate nurses with feelings of unpreparedness to care for, but it mobilizes to broaden the knowledge to provide care. There is evidence of a theory-practice dichotomy and weaknesses in teaching-learning experiences in undergraduate education.